Towards a Global Reconstruction of Indonesian Teacher Competencies: Integrating OECD and UNESCO Frameworks through Mixed Methods - Mufarahatus Syarifah; Rizki Amelia; Suyono Suyono; Oktaviani Adhi Suciptaningsih (Lembaga Bale Literasi, 2026)
This study aims to reconstruct Indonesian teacher competency standards by integrating global frameworks developed by the OECD and UNESCO through a mixed-methods approach. Using a sequential explanatory design, the study combined thematic analysis of policy documents, a Systematic Literature Review (SLR), and a quantitative survey involving 58 elementary school teachers in Malang Regency, Indonesia. The thematic analysis examined conceptual differences between national and global competency frameworks, while the SLR synthesized findings from 23 Scopus-indexed articles published between 2015 and 2026 concerning teacher competencies in global educational contexts. The survey measured teachers’ readiness in implementing both national and global competencies. The findings reveal that global teacher competencies have evolved toward multidimensional constructs encompassing pedagogical, digital, professional, social, and contextual dimensions, positioning teachers as transformative agents with reflective, collaborative, and innovative capacities. In contrast, Indonesian teacher competency standards remain predominantly focused on technical and administrative aspects. Survey results indicate that teachers demonstrate strong personal and social competencies, while pedagogical competence and readiness in global dimensions, particularly knowledge creation and digital pedagogy, remain relatively lower. The study proposes an integrative adaptation model that combines multidimensional competency reconstruction, ethical digital pedagogy, teacher agency, continuous professional development, and the integration of global perspectives with local wisdom. The findings provide theoretical contributions to the development of contextualized teacher competency models and practical implications for educational policy and teacher professional development in Indonesia.